Pengaruh Motivasi dan Kepmimpinan Terhadap Kinerja Karyawan pks PT Wilmar Nabati Dumai - Sulastri '; Marzolina '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to determine the performance of MCC employees at PT. Wilmar Vegetable Dumai with the aim to analyze the effect of variable motivation and leadership , employee performance against MCC at PT . Wilmar Bio- Dumai. Sampling was conducted using a census or a sample of 114 people saturated in use as a sample of respondents , the analysis method used is descriptive quantitative methods , data analysis carried out simultaneously and partial ( multiple linear regression analysis with SPSS version 19.0 ). From the results of simultaneous testing ( Test F ) , shows that all the independent variables studied had a significant impact on employee performance variables mcc . Partial regression test (t test ) showed that motivation variables significantly influence employee performance mcc at PT . Wilmar Bio- Dumai . The magnitude of the effect caused by these three variables together against the dependent variable was 96.4 % , this means that the variable motivation , and leadership , together affect employee performance variable with the percentage of 94.6 % mcc . While 3.6 % , influenced by other factors not participate in this study . Thus , it can be concluded that the motivation and leadership variables simultaneously and partially positive and significant impact on the performance of employees mcc at PT . Wilmar Bio- Dumai . In addition , also the motivation variable is a variable that has more influence on employee performance when compared with variable leadership .Keywords : Motivation , Leadership and employee performance mcc